Circadian blood pressure rhythm and increased body weight in patients with arterial hypertension and obstructive sleep apnoea syndrome - A. P. Ivanov; I. A. Elgardt; V. V. Rostorotskaya (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the specifics of 24-hour blood pressure monitoring (BPM) parameters and their association with body mass index (BMI) in patients with arterial hypertension (AH) and obstructive sleep apnoea (OSA) syndrome. Material and methods. The study included 120 AH patients with BMI under or over 25 kg/m2, who underwent 24-hour BMP and combined monitoring of electrocardiogram (ECG) and breathing. Results. AH patients with OSA syndrome demonstrated increased mean daytime and nighttime levels of systolic and diastolic BP (SBP, DBP) and a 1,5-fold increase in SBP and DBP pressure load indices. Patients with increased BMI had disturbed circadian BP profile, with reduced mean 24-hour difference, more pronounced for DBP (2,4-fold difference), and an increase in the “over-dipper” prevalence (from 13,3 % to 42,1 %). Conclusion. The combination of AH, OSA syndrome, and increased BMI substantially affected 24-hour BPM parameters. Increased BMI was associated with disturbed circadian BP profile and increased levels of mean 24-hour BP and nighttime BP